2014
DOI: 10.1007/s00438-014-0864-y
|View full text |Cite
|
Sign up to set email alerts
|

Homeologous genes involved in mannitol synthesis reveal unequal contributions in response to abiotic stress in Coffea arabica

Abstract: Polyploid plants can exhibit transcriptional modulation in homeologous genes in response to abiotic stresses. Coffea arabica, an allotetraploid, accounts for 75% of the world's coffee production. Extreme temperatures, salinity and drought limit crop productivity, which includes coffee plants. Mannitol is known to be involved in abiotic stress tolerance in higher plants. This study aimed to investigate the transcriptional responses of genes involved in mannitol biosynthesis and catabolism in C. arabica leaves u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 76 publications
0
24
0
Order By: Relevance
“…eugenioides subgenome (CaCe) instead of those from C . canephora (CaCc), as previously described for the citric acid cycle [63] and mannitol biosynthesis [64]. …”
Section: Discussionmentioning
confidence: 99%
“…eugenioides subgenome (CaCe) instead of those from C . canephora (CaCc), as previously described for the citric acid cycle [63] and mannitol biosynthesis [64]. …”
Section: Discussionmentioning
confidence: 99%
“…In another work, when the CaWRKY1a and CaWRKY1b genes that encode for transcription factors involved in the coffee defense responses to abiotic and biotic stresses were concomitantly expressed, both homeologous genes were found to contribute to the overall transcriptional level (Petitot et al 2008). Given the regulation mechanisms between homeologous genes, these studies and others (Carvalho et al 2014;Cotta et al 2014) demonstrated the complexity of regulation in allopolyploids and indicated that genes useful for C. arabica breeding programs could be present in its genome but have become inactive due to partitioned expression. However, one of the drawbacks of these studies was the lack of C. eugenioides data, which was necessary to increase and improve the comparison of gene expression of these subgenomes.…”
Section: Introductionmentioning
confidence: 87%
“…Primers were designed using Primer Express v.3.0 (Applied Biosystems), and qPCRs were run in a 7500 Fast Real-Time PCR System (Applied Biosystems) using the SYBR Green PCR Master Mix (Applied Biosystems). We followed the basic qPCR procedure described in a previous publication on coffee plants (Carvalho et al 2014).…”
Section: Qpcr Validation and Data Analysismentioning
confidence: 99%
“…One single or two homeologs were often predominantly expressed under normal and stress conditions. The uneven contribution of homeologs involved in mannitol synthesis has been reported in Coffea arabica 60 and the expression of the alcohol dehydrogenase A (AdhA) gene homeologs in allotetraploid cotton diverged significantly under multiple stresses 61 . The specific expression of homeologs during organ development and in response to stress conditions may benefit polyploid plants by allowing additional flexibility of response at the transcript level.…”
Section: Discussionmentioning
confidence: 99%